Acute idiopathic polyradiculoneuritis concurrent with acquired myasthenia gravis in a West Highland white terrier dog. Issue 1 (December 2016) - Stanciu, Gabriela; Solcan, Gheorghe
Abstract Background Acute Idiopathic Polyradiculoneuritis, an animal model for the axonal form of the Guillain – Barre Syndrome in humans and the acquired myasthenia gravis are different autoimmune disorders affecting the peripheral nerves and the neuromuscular junction, respectively. Both lead to muscle weakness and possible respiratory failure. The coexistence of these two entities combined in the same patient is rare in humans and, to our knowledge, the present case is the first reported in dogs. Case presentation An 11-year-old West Highland WhiteTerrier female dog was referred to our clinic with a history of symmetrical weakness beginning with the pelvic limbs and evolving cranially, progressing to non-ambulatory flaccid tetraparesis over the preceding week. The history did not reveal signs of a recent other illness, trauma or exposure to a neurotoxin or raccoon bite. The last vaccination was carried out 5 months before presentation. Upon clinical examination, spinal reflexes and postural reactions were decreased in all four limbs and became absent within the following 24 h; perineal reflex was normal, and loss of voice was observed. The patient maintained its ability to urinate and defecate and it had no difficulty to eat or to drink. There were no cerebellar or sensory deficits. The electrophysiological findings revealed positive sharp waves and complex repetitive discharges on the electromyogram, temporal dispersion of compound muscle action potentials associated with polyphasia and a slow motor nerve conduction velocity as signs of demyelination, and an increased latency of F-waves. The cerebrospinal fluid had a normal cellularity with increased protein content. A reduction by 18 % in the amplitudes of the third compound muscle action potential as compared to the first one was observed during a repetitive nerve stimulation, indicating a postsynaptic disturbance. Only the motor electrophysiology was considered in this study. The diagnosis was based on clinical and electrophysiological findings associated with a positive titer for acetylcholine receptor antibodies. Conclusion The diagnosis of MG was based on the typical clinical findings such as dysphonia and dysphagia, decremental response of RNS and positive AChRs antibody titre. Flaccid tetraparesis associated with diminished reflexes, increase of the distal latencies and temporal dispersion which caused lower MNCV, along with the increase of the F wave latencies supported the diagnosis of AIP. A cerebrospinal fluid tap indicated an albuminocytologic dissociation sustaining the radicular implication of AIP. As such, a diagnosis of MG and AIP co-occurrence syndrome was established.